Alliance formation: A Study of the Malaysian Automobile Supporting Industry - Abdul Ghani, Ahmad Bashawir; Tull, Malcolm (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
CompetitionÂ inÂ globalÂ industriesÂ isÂ shiftingÂ increasingly fromÂ inter-firmÂ rivalryÂ toÂ rivalryÂ betweenÂ networksÂ ofÂ firms. Strategies of individualÂ firms are thus contingent on the degree of interdependence that exists between them and the parent firm in the network. The present study examines the effect of network affiliation on a member firmâs decision to enter a foreign market andÂ internationalÂ strategicÂ allianceÂ formation.Â AffiliateÂ firms have two options available to them: (1) enter into a competitive strategic alliance with a competitor or (2) enter into a symbioticstrategic alliance withÂ the parent firm of the network organiza-tion.Â We testedÂ this assertionÂ usingÂ dataÂ from archivalÂ sources onÂ sixty-fiveÂ JapaneseÂ automobileÂ suppliersÂ thatÂ hadÂ setÂ up strategicÂ alliancesÂ inÂ MalaysiaÂ andÂ thatÂ belongedÂ toÂ various inter-organizationalÂ networks.Â ResultsÂ indicateÂ thatÂ whenÂ affili-ate firms are dependent on the parent firm, they prefer to form symbioticÂ strategicÂ alliances.Â Conversely,Â affiliateÂ firmsÂ prefer competitiveÂ strategicÂ alliancesÂ withÂ competitorsÂ whenÂ theyÂ are notÂ dependentÂ onÂ theÂ parentÂ firm. ALLIANCEÂ FORMATIONA Study of the Malaysian Automobile Supporting IndustryKeywords: automobile industry; joint venture; mode of entry; networks; strategic alliances